2017
DOI: 10.1093/pch/pxx091
|View full text |Cite
|
Sign up to set email alerts
|

Audit of pulse oximetry screening for critical congenital heart disease (CCHD) in newborns

Abstract: The current study shows that screening was successfully implemented in a Canadian hospital, with high specificity (99.4%) and good compliance (88%). Reasons for non-acceptance of screening by midwives need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…In one recent report from a center where the practice of routine pulse oximetry screening for congenital heart disease was adopted and then audited, compliance with their protocol was 88%, which is good but not optimal. 25 The association of late diagnosis with MACE after repair of truncus arteriosus in our study and the aforementioned data on the benefits of routine pulse oximetry screening for congenital heart disease support the further expansion of this practice and the establishment of infrastructure at the local level to ensure that these programs are operating appropriately.…”
Section: Discussionsupporting
confidence: 73%
“…In one recent report from a center where the practice of routine pulse oximetry screening for congenital heart disease was adopted and then audited, compliance with their protocol was 88%, which is good but not optimal. 25 The association of late diagnosis with MACE after repair of truncus arteriosus in our study and the aforementioned data on the benefits of routine pulse oximetry screening for congenital heart disease support the further expansion of this practice and the establishment of infrastructure at the local level to ensure that these programs are operating appropriately.…”
Section: Discussionsupporting
confidence: 73%
“…Our results showed that PO had a sensitivity of 100%, a specificity of 100%, a positive predictive value of 100%, and a negative predictive value of 100% in comparison to Echocardiography as a gold standard test. In line with our results Lightfoot et al, the specificity was 99.4% while the sensitivity were not applicable (16). In contrary Danworapong et al found the sensitivity of PO was 42.86% and a specificity of 99.96% (17), the sensitivity was lower than that in our studies because of a high percentage of cases diagnosed as coarctation of the aorta (COA) (57.1%) in this study; it is known that COA has a low sensitivity of POS for CCHD (36%-53.3%).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, Name of the author [25] discovered that Pulse oximetry (PO) offers 100% sensitivity, 100% specificity, 100% positive predictive value, and 100% negative predictive value-when compared to echocardiography, the gold standard test. That was by Name of the author [26] reported that the sensitivity was not applicable, and the specificity was 99.4%. On the other hand, Name of the author [27] discovered that the specificity was 99.96% and the sensitivity of PO was 42.86%.…”
Section: Discussionmentioning
confidence: 98%